Callirhoe, Concubinage, and a Corruption in Chariton 2.11.5 - Trzaskoma, Stephen M. (Exemplaria Classica, 2017)
The author posits an unnoted textual corruption in Chariton 2.11.5 (?? ?? ????? ??????????) and, based on palaeography, the surrounding context, and an internal parallel, proposes a correction (?? ?? ???? ??????????).